Interdisciplinary Work Is Essential for Research on Puberty: Complexity and Dynamism in Action - Susman, Elizabeth J. (J Res Adolesc, 2019)
Puberty is associated with changes in behavior and psychosocial well-being, and is important in lifelong health. We present five different facets regarding interdisciplinary research that are important to puberty. A short history of philosophical issues instrumental in promoting early interdisciplinary research is first presented. We discuss then what is hard and what is easy about interdisciplinary research, the purpose of which is to alert scientists to challenges and opportunities for interdisciplinary research on puberty. Readers then are introduced to advances and obstacles in interdisciplinary research on development. Recommendations for tailoring graduate education toward interdisciplinarity are introduced. Finally, issues related to publication, education of scientists, and policy makers are described. The report concludes with a discussion of funding and policy issues.